Dose response relationship between whole body vibration (WBV) and low back pain (LBP) among different types of vehicular drivers in the state of Sabah / Anisah Jantim - Anisah, Jantim (2018)
Effect of whole body vibration (WBV) to the human spine is determined by a combination of vibration magnitude and duration of exposure. This study aimed to ascertain the dose response relationship between WBV and low back pain (LBP) among drivers in state of Sabah. A cross sectional study was conducted among 155 male drivers (predominantly Kadazan/Dusun) operating a different type of vehicles. Measurements of WBV exposures were conducted in strict compliance with ISO 2631-1 requirements. A structured interview using a standardized questionnaire was conducted to assess LBP, individual characteristics, and other work-related risks factor. Postural risks to LBP were assessed via direct observation. Vibration exposures were calculated based on a daily [acceleration equivalent over an eight hours reference period express in A(8) for root-mean-square (r.m.s) and Vibration Dose Value (VDV) for root-mean-quad (r.m.q)] and cumulative measures [acceleration express in the form of ∑ai mT where ai is the means of vibration magnitude in aws and awq (frequency weighted in r.ms and r.m.q respectively), T is the total hours of exposure and m in the order of zero, one, two or four]. The log form of the doses divided into four quartiles and regressed against a symptom of LBP. Based on health risks analysis following the health guidance caution zone (HGCZ) severe form of daily WBV exposures expressed in VDV as about 99.4% exceeded the recommended values as opposed to daily exposures expressed in A(8) as only 9.0%. At univariate analysis, several individual factors (higher education attainment, non-alcoholic, smoking and presence of MSD other than lower back region) and work-related factors (involvement in part-time job, work schedule following office hours and posture against backrest while driving) were significantly associated with symptoms of LBP. In the multiple logistic regressions after adjustment of the potential confounders, there was a significant increase in the odds of developing LBP with WBV observed using the cumulative dose measures. At LBP past 12 months drivers exposed to Dose 3 and Dose iv 6 [ln(aws) 2T and ln(awq) 2T] in quartile two reported with (aOR = 2.822, 95% C1 1.038 to 7.668) and (aOR = 2.981, 95% CI 1.096 to 8.104) respectively. At LBP past four weeks drivers exposed to Dose 2, Dose 3, Dose 5 and Dose 6 [ln(aws)T, ln(aws) 2T, ln(awq)T and ln(awq) 2T] in quartile two reported with (aOR= 3.667, 95% CI 1.399 to 9.613), (aOR= 2.649, 95% CI 1.206 to 6.838), (aOR = 3.303, 95% CI 1.273 to 8.570) and (aOR = 3.852, 95% CI 1.455 to 10.193) respectively. In the occurrence of LBP post driving, only one statisticallyly significant result observed at quartile two for Dose 2 [ln(aws)T] with (aOR = 4.208, 95% CI 1.442 to 12.277). The finding indicates dose response relationship between increasing exposures of WBV and occurrence of LBP among professional drivers. The first [ln(aws)T and ln (awq)T] and second [ln(aws) 2T ln(awq) 2T] orders for cumulative dose measures were more predictive in comparison to daily measures of A(8) and VDV.